An In-Depth Analysis of Public and Private Research Funding in Orthopaedic Surgery from 2015 to 2021 - Shah, Aakash K; Burkhart, Robert J; Shah, Varunil N; Gould, Heath P; Acuña, Alexander J; Kamath, Atul F (Journal of bone and joint surgery. American volume, 2024)
Understanding the trends and patterns of research funding can aid in enhancing growth and innovation in orthopaedic research. We sought to analyze financial trends in public orthopaedic surgery funding and characterize trends in private funding distribution among orthopaedic surgeons and hospitals to explore potential disparities across orthopaedic subspecialties. We conducted a cross-sectional analysis of private and public orthopaedic research funding from 2015 to 2021 using the Centers for Medicare & Medicaid Services Open Payments database and the National Institutes of Health (NIH) RePORTER through the Blue Ridge Institute for Medical Research, respectively. Institutions receiving funds from both the NIH and the private sector were classified separately as publicly funded and privately funded. Research payment characteristics were categorized according to their respective orthopaedic fellowship subspecialties. Descriptive statistics, Wilcoxon rank-sum tests, and Mann-Kendall tests were employed. A p value of <0.05 was considered significant. Over the study period, $348,428,969 in private and $701,078,031 in public research payments were reported. There were 2,229 unique surgeons receiving funding at 906 different institutions. The data showed that a total of 2,154 male orthopaedic surgeons received $342,939,782 and 75 female orthopaedic surgeons received $5,489,187 from 198 different private entities. The difference in the median payment size between male and female orthopaedic surgeons was not significant. The top 1% of all practicing orthopaedic surgeons received 99% of all private funding in 2021. The top 20 publicly and top 20 privately funded institutions received 77% of the public and 37% of the private funding, respectively. Private funding was greatest (31.5%) for projects exploring adult reconstruction. While the amount of public research funding was more than double the amount of private research funding, the distribution of public research funding was concentrated in fewer institutions when compared with private research funding. This suggests the formation of orthopaedic centers of excellence (CoEs), which are programs that have high concentrations of talent and resources. Furthermore, the similar median payment by gender is indicative of equitable payment size. In the future, orthopaedic funding should follow a distribution model that aligns with the existing approach, giving priority to a nondiscriminatory stance regarding gender, and allocate funds toward CoEs. Securing research funding is vital for driving innovation in orthopaedic surgery, which is crucial for enhancing clinical interventions. Thus, understanding the patterns and distribution of research funding can help orthopaedic surgeons tailor their future projects to better align with current funding trends, thereby increasing the likelihood of securing support for their work.